Mining law & regulatory practice in Indonesia : a primary reference source - Sullivan, Bill.; Purwono, Christian Teo.; Harwood, Stephenson (Singapore : Wiley, 2013)
The first and only English-language reference to the laws and regulations of the booming Indonesian mining sector As the growing Indonesian mining industry attracts new investment from foreign mining companies, those companies are faced with the daunting challenge of unraveling the hugely confusing and complex plethora of local laws and regulations that govern the industry. Until now, there has been no comprehensive English-language guide to Indonesia's mining laws that western companies could turn to for reliable guidance and advice. This detailed reference fills that gap for the min.
4. Implementation of Prioritization of Mineral and Coal Supply for Domestic Interest.
Includes index.
Online resource; title from title page (ebrary, viewed July 23, 2013).
John Wiley and Sons
Keywords: Mining law -- Indonesia; LAW -- Military; Mining law; Indonesia